2019
DOI: 10.2217/fon-2018-0964
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Agents or Immuno-Oncology Therapies as First-Line Therapy for BRAF-Mutated Metastatic Melanoma: A Real-World Study

Abstract: Aim: Targeted therapy (TT) and immuno-oncology (IO) drugs are approved for patients with BRAF mutant metastatic melanoma (MM). We compared real-world outcomes for first-line (1L) TT versus 1L IO to evaluate optimal sequencing. Materials & methods: Physicians-identified BRAF mutant MM patients initiating 1L TT or IO therapies and extracted treatment, disease and clinical outcomes including disease response which were compared between TT and IO and individual regimens. Results: 440 MM patients (TT = 283, IO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
4
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 23 publications
4
39
4
4
Order By: Relevance
“…The proportions of patients advancing from 1L to 2L and 3L are consistent with similar studies of community‐based care of melanoma. In the real‐world study of patients with BRAF‐mutant advanced melanoma initiating 1L treatment, Luke et al (2019) reported that only 49.8% received 1L treatment, 43.5% received both 1L and 2L, and only 6.7% received 3L 29 . In another real‐world study of treatment‐naïve patients with BRAF‐mutant advanced melanoma, Whitman et al (2019) found that 57.0% of the BRAF‐mutant cohort received only 1L, 28.0% 1L and 2L, and 15.0% 3L+ 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of patients advancing from 1L to 2L and 3L are consistent with similar studies of community‐based care of melanoma. In the real‐world study of patients with BRAF‐mutant advanced melanoma initiating 1L treatment, Luke et al (2019) reported that only 49.8% received 1L treatment, 43.5% received both 1L and 2L, and only 6.7% received 3L 29 . In another real‐world study of treatment‐naïve patients with BRAF‐mutant advanced melanoma, Whitman et al (2019) found that 57.0% of the BRAF‐mutant cohort received only 1L, 28.0% 1L and 2L, and 15.0% 3L+ 26 .…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the opportunity to discuss and clarify our findings [1]. Although the letter authors' work complements our own [2][3][4][5], the objectives and the methods differ. For example, in Feinberg et al, Response Evaluation Criteria in Solid Tumors (RECIST) was applied to realworld imaging data that were submitted in case report forms by compensated physicians.…”
Section: To the Editormentioning
confidence: 99%
“…With the advent of immunotherapies, the tumor's management has shifted from cytokine-based treatment to immune checkpoint inhibition, primarily of cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) and programmed cell-death protein 1 (PD-1) or its ligands (PD-L1 and PD-L2) [15][16][17][18]. Monoclonal antibodies including Ipilimumab, Tremelimumab (anti-CTLA-4), Pembrolizumab, Nivolumab, Cemiplimab (anti-PD-1), Atezolizumab, Avelumab and Durvalumab (anti-PD-L1), among others currently being on clinical trial [19], have enthusiastically provided longlasting responses and improved survival in patients with advanced-stage metastatic melanoma [16].…”
Section: Introductionmentioning
confidence: 99%